PROFILING LEARNING ACTIVITIES IN EXTENSIVE READING COURSE: A CASE OF INDONESIAN UNIVERSITY LEARNERS - Rufaidah Al Anshoriah; Soni Tantan Tandiana; Fuad Abdullah (TLEMC (Teaching and Learning English in Multicultural Contexts), 2019)
Extensive Reading (hereafter, ER) has been discussed and deployed as a prevalent approach to enhance EFL/ESL learners’ reading skills in language classroom for several decades. However, insufficient attention has been devoted to the students’ learning activities in Extensive Reading course, notably in Indonesia. For this reason, this study accentuated on profiling the learning activities in Extensive Reading course in such a country. The data were collected through semi-structured interview and analysed with thematic analysis (Braun Clarke, 2006). The findings designated that the students performed two main learning activities in Extensive Reading course, namely inside and outside classroom activities. Viewed from inside classroom activities, they conducted classroom presentations to develop not only reading skills but also speaking skills, self-confidence and self-responsibilities. On the other hand, they selected and read literary works based on their interests and abilities, completed reading logs, created powerpoint slides, made a written reports, produced a poster for presentations and posted their works on their own blogs. Given these facts, ER learning activities enable the EFL/ESL learners to foster and sustain their reading strategies and become more strategic readers.